Faktor–Faktor yang Mempengaruhi Ketidakakuratan External Cause pada Diagnosis Cedera di RSU Thalia Irham Panciro Kabupaten Gowa Triwulan I Tahun 2025 - Haerunnisa Haerunnisa; Ahmad Jayadie; Hidayati Ismail; Agustina Agustina (Inovasi Kesehatan Global, 2025)
Background: Accurate coding of external cause in injury diagnoses is crucial to ensure the validity of medical records, support health policy decisions, and maintain the quality of morbidity reporting.  Objective: To determine the factors that influence the inaccuracy of external cause codes in injury diagnosis at Thalia Irham General Hospital, Panciro, Gowa Regency. Method: This study employed a descriptive qualitative approach using observation and in-depth interviews with outpatient coders handling injury cases. Result: The study found that only 36% of the medical record documents were coded accurately, 26% were inaccurately coded, and 36% lacked any external cause code. The main causes of inaccuracy included incomplete anamnesis, limited time, absence of specific standard operating procedures (SOPs), and the belief that external cause codes do not impact BPJS claims. Conclusion: The low level accuracy of external cause coding is caused by the lack of understanding of officers regarding the ICD-10 Chapter XX classification, the absence of a specific SOP for coding injuries, and the perception that external cause codes do not affect the claims system.